1997
DOI: 10.1063/1.1148380
|View full text |Cite
|
Sign up to set email alerts
|

A new x-ray diffraction method for structural investigations of solid-liquid interfaces

Abstract: A synchrotron x-ray diffraction method is presented for structural investigations of interfaces between low-Z substrates and heavier liquids. The method, similar to methods used in neutron scattering, is based on illuminating the interface through the solid substrate. The backgrounds arising from bulk scattering and the signal-to-background ratio are estimated and compared with experimental results. An ultrahigh vacuum ͑UHV͒ setup is described in which the atomic arrangement and roughness of clean interfaces c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…They indicated that at large interactions substantial epitaxial ordering happens and the first or two fluid layers become locked to the wall. Huisman et al [48] investigated structure of solid-liquid interface with a synchrotron X-ray diffraction method. The method can be effective because of deep penetration of x-rays in matter.…”
Section: Solid-liquid Interfacial Layermentioning
confidence: 99%
“…They indicated that at large interactions substantial epitaxial ordering happens and the first or two fluid layers become locked to the wall. Huisman et al [48] investigated structure of solid-liquid interface with a synchrotron X-ray diffraction method. The method can be effective because of deep penetration of x-rays in matter.…”
Section: Solid-liquid Interfacial Layermentioning
confidence: 99%
“…Because in reflection geometry the beam has to penetrate several millimeters of Al 2 O 3 , high-energy X-rays are essential. 114116…”
Section: X-ray Surface Forces Apparatusmentioning
confidence: 99%
“…The TCF and other spatial functions can be experimentally measured with x-ray diffraction[31], inelastic scattering of thermal neutrons[32], light scattering[1] and electron diffraction[33] experiments.…”
Section: Integral Equationsmentioning
confidence: 99%